Resonant acoustic mixing-assisted fabrication and evaluation of FDM-printed PLA/β-TCP scaffolds for bone tissue engineering - Zhu, Yixuan; Hu, Jiangqi; Luo, Bin; Deng, Xuening; Xie, Siyu; Huang, Jiuning; Yuan, Yafei; Jiang, Qingsong (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundComposite scaffolds combining polylactic acid (PLA) with β-tricalcium phosphate (β-TCP) offer potential for bone tissue engineering (BTE) by integrating mechanical support with bioactivity. However, the optimal ratio balancing biological performance, structural integrity, and manufacturing feasibility remains unclear.MethodsPLA/β-TCP composites containing 0%, 10%, 20%, and 30% β-TCP were prepared using solvent-free resonant acoustic mixing (RAM), extruded into filaments, and printed by fused deposition modeling (FDM). Scaffolds were evaluated for mechanical properties, printability, and in vitro biocompatibility with rat bone marrow mesenchymal stem cells (rBMSCs). Osteogenic differentiation was assessed by ALP activity, calcium deposition, and expression of osteogenic marker. In vivo bone regeneration was investigated in a rat calvarial defect model.ResultsAll β-TCP-containing scaffolds enhanced cell adhesion, proliferation, and osteogenesis compared with pure PLA. The 80:20 PLA/β-TCP scaffold showed optimal balance of bioactivity, compressive strength, and printing quality. Excessive β-TCP (>20%) reduced mechanical strength and caused printing defects. In vivo, the 80:20 group showed superior early bone regeneration after 4 weeks, confirmed by micro-CT and histology.ConclusionThe 80:20 PLA/β-TCP composition offers an optimal balance of biological activity, mechanical performance, and manufacturing scalability, supporting its potential as a cost-effective scaffold for clinical BTE applications.